ADAPTING A DUAL HIGHER EDUCATION SYSTEM IN VILNIUS COLLEGE OF TECHNOLOGIES AND DESIGN: THE CASE OF UNIVERSITY OF SZEGED - Ginavičienė, Jurgita; Vitkūnas, Rolandas; Gál, József; Bíró, István (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The system of higher education in the European Union based on legal instruments valid for all States Member. However, each EU State Member has additional national legislation, which taken into account in the design of the higher education system. The design and implementation of study programs is one of the activities of higher education. Compliance with EU and national legislation are important in design of study programs. It is equally important that the programs are necessary for the national economy, companies and attractive to students. The aim of the article is to determine the need and possibilities of dual teaching in the study program Transport Logistics of Vilnius College of Technology and Design. The structure of curricula of dual education at Szeged University in Hungary is analysed. The indicators of changes in studies and practical training from the point of view of students and companies at Szeged University are present.The article presents a comparative analysis of legislation, study programs and business needs in Lithuania. The analysis showed that business enterprises in Lithuania would be interested in dual training; the application of dual training is not in principle contrary to Lithuanian legislation.